Pointed rhythmic theta waves: a unique EEG pattern in KCNQ2‐related neonatal epileptic encephalopathy. Issue 3 (31st October 2017) - Buttle, Sarah Grace; Sell, Erick; Dyment, David; Bulusu, Srinivas; Pohl, Daniela
Abstract: We report the case of an infant with KCNQ2‐related neonatal epileptic encephalopathy presenting with intractable seizures beginning on the second day of life, which were resistant to multiple antiepileptic drugs. Continuous EEG recordings starting on the sixth day of life demonstrated a unique pattern of inter‐and postictal focal rhythmic pointed theta waves of lambdoid morphology in the immediate postictal period, localizing to the side of the antecedent seizure. Interictal EEG exhibited discontinuous background, including patterns of burst suppression and multifocal discharges, predominantly in the centrotemporal regions, which were aggravated during sleep. MRI demonstrated T1 signal abnormalities in the basal ganglia, bilaterally. Genetic testing revealed a de novo missense mutation in KCNQ2 at position c.545 T>G, encoding a previously unreported substitution (p.Val182Gly). Seizure control was achieved immediately after starting a lidocaine infusion at age 4 weeks. The patient remained largely seizure‐free following add‐on oral carbamazepine for maintenance therapy and weaning off lidocaine. This is the first report of a patient with KCNQ2‐related neonatal epileptic encephalopathy and therapy‐refractory seizures aborted by lidocaine, demonstrating a unique EEG pattern of inter‐ and postictal focal rhythmic pointed theta waves. Whether this pattern could be an early EEG marker for this disorder remains to be confirmed. [ Published with video sequences on www.epilepticdisorders.com ]